2004
DOI: 10.1002/ejoc.200400234
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Applications of Intermolecular Cyclopropanation of Carboxylic Esters with Dialkoxytitanacyclopropane Reagents

Abstract: The reaction of carboxylic esters with ethylmagnesium bromide in the presence of titanium(iv) isopropoxide, which leads to the formation of substituted cyclopropanols, was disclosed in the late 1980Јs. The key organometallic intermediates in this transformation are diisopropoxytitanacyclopropane species, which act as 1,2-dicarbanionic equivalents. The intermolecular titanium-mediated cyclopropanation of carboxylic esters and subsequent transformation of the threemembered ring provides a convenient and flexible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…[17] Indeed, the oxime ethers were converted into the corresponding NH-azetidines with the olefins incorporated into the product and yields of up to 42 %(4, 30-33). If this mechanism is viable,l igand exchange should occur between the olefin and the titanacyclopropane intermediate.…”
Section: Zuschriftenmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Indeed, the oxime ethers were converted into the corresponding NH-azetidines with the olefins incorporated into the product and yields of up to 42 %(4, 30-33). If this mechanism is viable,l igand exchange should occur between the olefin and the titanacyclopropane intermediate.…”
Section: Zuschriftenmentioning
confidence: 99%
“…If this mechanism is viable,l igand exchange should occur between the olefin and the titanacyclopropane intermediate. [17] Indeed, the oxime ethers were converted into the corresponding NH-azetidines with the olefins incorporated into the product and yields of up to 42 %(4, 30-33). Interestingly,substitution on the 2-position of the terminal olefin was tolerated to provide the azetidine 32 in moderate yield.…”
Section: Communicationsmentioning
confidence: 99%
“…[218][219][220] Scheme 33 Reduction of Thioamides by Raney Nickel [219,220] In his original experiments, Kulinkovich treated carboxylic acid esters with a Grignard reagent and titanium(IV) isopropoxide to obtain cyclopropanol derivatives. [221][222][223] The scope of this transformation was expanded by de Meijere, who demonstrated that N,N-disubstituted amides of carboxylic acids also undergo cyclopropanation upon treatment with Grignard reagents and titanium(IV) isopropoxide. [174] The latter reaction was therefore named the Kulinkovich- Because the oxotitanium oligomers 129 are further transformed into titanium(IV) oxide, at least 1 equivalent of titanium(IV) isopropoxide is necessary to achieve good yields of the cyclopropanamine.…”
Section: Variation 3: Reduction With Hydrosilanesmentioning
confidence: 99%
“…The latter can be generated directly from titanium(IV) alkoxides and the corresponding Grignard reagents [3,5] иor by the ligand exchange at the titanium(II) atom [4,5]. Some cyclopropanol derivatives we have successfully used in the synthesis of natural bioactive compounds [6].…”
mentioning
confidence: 99%